Vibration of the Whole Foot Soles Surface Using an Inexpensive Portable Device to Investigate Age-Related Alterations of Postural Control - Lauzier, Lydiane; Kadri, Mohamed Abdelhafid; Bouchard, Emilie; Bouchard, Kevin; Gaboury, Sébastien; Gagnon, Jean-Michel; Girard, Marie-Pier; Larouche, Andréanne; Robert, Roxane; Lapointe, Patrick; da Silva, Rubens A.; Beaulieu, Louis-David (Frontiers in Human Neuroscience, 2021)
Background: Standing on a foam surface is used to investigate how aging affect the ability to keep balance when somatosensory inputs from feet soles become unreliable. However, since standing on foam also affects the efficacy of postural adjustments, the respective contributions of sensory and motor components are impossible to separate. This study tested the hypothesis that these components can be untangled by comparing changes of center of pressure (CoP) parameters induced by standing on a foam pad vs. a novel vibration (VIB) platform developed by our team and targeting feet soles’ mechanoreceptors. Methods: Bipedal postural control of young (n=20) and healthy elders (n=20) was assessed while standing barefoot on a force platform through 3 randomized conditions: 1) Baseline (BL); 2) VIB; and 3) Foam. CoP Amplitude and Velocity in the antero-posterior/medio-lateral (AP/ML) directions and COP Surface were compared between conditions and groups. Findings : Both VIB and Foam increased CoP parameters compared to BL, but Foam had a significantly greater impact than VIB for both groups. Young and Old participants significantly differed for all three Conditions. However, when correcting for BL levels of postural performance, VIB-related increase of COP parameters was no longer different between groups, conversely to Foam. Interpretation: Although both VIB and Foam highlighted age-related differences of postural control, their combined use revealed that ‘motor’ and ‘sensory’ components are differently affected by aging, the latter being relatively unaltered, at least in healthy/active elders. The combined used of these methods could provide relevant knowledge to better understand and manage postural impairments in the aging population.